Technology and acoustical properties of the ceramic high-temperature superconductors - ALEKSIEJUK, M.; RAABE, J.; RANACHOWSKI, J. (Archives of Acoustics, 1991)
The aim of this paper is to present the acoustic methods of investigating the phenomena taking place in the range of the conductor-superconductor transition in the selected ceramic superconducting materials.